Copper - Fairweather-Tait, Susan (Henry Stewart Talks, 2025)
Function of copper in the body, Food sources of copper, Copper deficiency and Menkes syndrome, Wilson’s disease, Copper absorption and metabolism in the body, Excess copper, Dietary reference values for copper